The Intergenic Recombinant HLA-B∗46:01 Has a Distinctive Peptidome that Includes KIR2DL3 Ligands - Hilton, Hugo G. (2017)
HLA-B∗46:01 was formed by an intergenic mini-conversion, between HLA-B∗15:01 and HLA-C∗01:02, in Southeast Asia during the last 50,000 years, and it has since become the most common HLA-B allele in the region. A functional effect of the mini-conversion was introduction of the C1 epitope into HLA-B∗46:01, making it an exceptional HLA-B allotype that is recognized by the C1-specific natural killer (NK) cell receptor KIR2DL3. High-resolution mass spectrometry showed that HLA-B∗46:01 has a low-diversity peptidome that is distinct from those of its parents. A minority (21%) of HLA-B∗46:01 peptides, with common C-terminal characteristics, form ligands for KIR2DL3. The HLA-B∗46:01 peptidome is predicted to be enriched for peptide antigens derived from Mycobacterium leprae. Overall, the results indicate that the distinctive peptidome and functions of HLA-B∗46:01 provide carriers with resistance to leprosy, which drove its rapid rise in frequency in Southeast Asia.